Laminate circular cylindrical shell - Kormaníková Eva; Kotrasová Kamila (MATEC Web of Conferences, 2017)
The paper deals with a numerical approach of optimal design modelling of laminate circular cylindrical shell. For thin-walled shells the classical shell theory is capable of accurately predicting the shell behaviour. In the frame of numerical optimization of circular cylindrical shell there is made the minimization of weight subject to displacement constraint. Thickness of layers is taken as design variable. In the example there is found the thickness of the shell laminate roof under constant pressure loading using Modified Feasible Direction method.